Feature Papers in Bioactives and Nutraceuticals (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This Reprint aims to immerse the readers into the latest frontiers of cutting-edge investigations regarding bioactive compounds and nutraceuticals. It explores their use in biotechnological approaches, biomedical applications, the discovery of novel bioactive natural products, the role of these products on food structure, and their potential physiological effects on human nutrition. Additionally, it discusses the use of in vitro and in vivo bioactivity research involving cell lines and animal models as exemplars of human physiology.